Gendering the history of foreign correspondents: The case of Helsingin Sanomat’s Maija-Liisa Heini - Kurvinen Heidi (Norway, 2023)
Maija-Liisa Heini (1917–1988) was a star reporter of her time who spent most of her career working at the biggest national newspaper in Finland, Helsingin Sanomat. In this article, I focus on Heini’s work during the late 1960s as the paper’s Scandinavian correspondent. More specifically, I will use Heini as a case study to unravel the gendered history of foreign correspondence by adopting Lonsdale’s argument that early women correspondents’ outsider status allowed them to produce alternative narratives of foreign affairs. By analysing news and feature articles written by Heini, I argue that she used her status as a journalist of high standing to disrupt existing ideas about what constituted good foreign news journalism. In doing so, she was successful in combining a so-called feminine writing style with a professional persona that embraced masculine traits of journalism.